The impact of low to moderate alcohol consumption on different types of human performance - Goble, David (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2013)
Despite extensive research into the effects of alcohol consumption, there is no clear understanding into the mechanisms underlying human information processing impairment. The acute consumption of alcohol was investigated to determine the implications for human information processing capabilities, and to identify the extent to which these implications were stage-specific. Further aims included the investigation and quantification of caffeine-induced antagonism of alcohol impairment. Moreover, the aforementioned relationships were investigated in morning versus evening conditions. A test battery of six resource-specific tasks was utilised to measure visual perceptual, cognitive and sensory-motor performance, fashioned to return both simple and complex measures of each task. The tasks implemented were: visual perceptual performance (accommodation, visual detection, visual pattern recognition); cognition (memory recall- digit span); and motor output (modified Fitts"Ÿ and a driving simulated line-tracking). Performance measures were recorded by the respective computer based tasks. Physiological variables measured included heart rate frequency, heart rate variability (RMSSD, High and Low Frequency Power) and body temperature. Saccade speed, saccade amplitude, pupil size and fixation duration were the oculomotor parameters measured. Three groups of participants (alcohol, caffeine+alcohol and control) n=36 were studied, split evenly between sexes in a mixed repeated/non-repeated measures design. The control group performed all test batteries under no influence. The alcohol group performed test batteries one and two sober, and three and four under the influence of a 0.4 g/kg dose of alcohol. Group caffeine+alcohol conducted test battery one sober, two under the effect of caffeine only (4 mg/kg), and three and four under the influence of both caffeine and alcohol (0.4 g/kg). The third test battery demonstrated the effects of alcohol during the inclining phase of the blood alcohol curve, and the fourth represented the declining phase. Morning experimentation occurred between 10:00 - 12: 45 and 10:30 -13:15 with evening experimentation between 19:00 - 21:30 and 19:30 - 22:00. Acute alcohol consumption at a dose of approximately 0.4 g/kg body weight effected an average peak breath alcohol concentration of 0.062 % and 0.059 % for the alcohol and caffeine+alcohol groups respectively. Task-related visual perceptual performance demonstrated significant decrements for simple reaction time, choice reaction time and error rate. Cognitive performance demonstrated no significant performance decrements, while motor performance indicated significant decrements in target accuracy only. Physiological parameters in response to alcohol consumption showed significantly decreased heart rate variability (RMSSD) in the modified Fitts"Ÿ task only. A significant decrease in saccade amplitude in the memory task was the only change in oculomotor parameters. Prior caffeine consumption demonstrated limited antagonism to task-related alcohol impairment, significantly improving performance only in reduced error rate while reading. Caffeine consumption showed stimulating effects on physiological parameters, significantly increasing heart rate and heart rate variability when compared to alcohol alone. The design of the tasks allows for comparison between complex and simple task performance, indicating resource utilisation and depletion. Complex tasks demonstrated higher resource utilisation, however with no statistical performance differences to simple tasks. Physiological parameters showed greater change in response to alcohol consumption, than did the performance measures. Alcohol consumption imposed significant changes in physiological and oculomotor parameters for cognitive tasks only, significantly increasing heart rate frequency and decreasing heart rate variability, skin temperature and saccade amplitude. Caffeine consumption showed no antagonism of alcohol-induced performance measures. Physiological measures showed that caffeine consumption imposed stimulating effects in only the neural reflex and memory tasks, significantly increasing heart rate frequency and heart rate variability. Prior caffeine consumption significantly decreased fixation duration in the memory task only. The time of day at which alcohol was consumed demonstrated significant performance and physiological implications. Results indicated that morning consumption of alcohol imposes greater decrements in performance and larger fluctuations in physiological parameters than the decrements in evening experimental sessions. It can be concluded that alcohol consumption at a dose of 0.4 g/kg affects all stages in the information processing chain. Task performance indicates that alcohol has a greater severity on the early stages of information processing. Conversely, under the influence of alcohol an increased task complexity induces greater effects on central stage information processing. In addition, caffeine consumption at a dose of 4 mg/kg prior to alcohol does not antagonise the alcohol-induced performance decrements.
Keywords: Alcohol -- Physiological effect; Temperance; Human information processing -- Effect of drugs on; Visual perception -- Effect of drugs on; Cognition -- Effect of drugs on; Caffeine -- Physiological effect